New insights into the natural history of hepatitis E virus infection through a longitudinal study of multitransfused immunocompetent patients in France. Issue 7 (18th March 2016) - Servant‐Delmas, A.; Abravanel, F.; Lefrère, J.‐J.; Lionnet, F.; Hamon, C.; Izopet, J.; Laperche, S.
Summary: Little is known about the natural history of Hepatitis E virus (HEV) infection in immunocompetent individuals. The prevalence, the course of infection and the occurrence of transmission by transfusion were investigated in multitransfused immunocompetent patients/blood donor pairs included in a longitudinal sample repository collection and followed up between 1988 and 2010. Ninety‐eight subjects aged 6–89 years and suffering from acquired haemoglobinopathies were tested for HEV markers (IgM, IgG and RNA) in serial samples collected every 2 or 3 years. Eighteen patients (18.4%) were positive for HEV‐IgG at baseline with a prevalence increasing from 12.5% below 26 years to 32% above 56 years. Nine patients remained IgG positive along the study and nine lost their antibodies after a mean follow‐up of 7.4 years (1–22 years). One seropositive patient showed an increase of IgG level and RNA‐HEV reappearance 1 year after inclusion, suggesting a reinfection and one seroconversion, probably acquired through blood transfusion was observed. This first longitudinal study including immunocompetent individuals confirms that HEV infection is common in Western Europe and that transfusion transmission occurs probably less frequently than expected. In addition, seroreversion and reinfection seem to be common. This suggests that the anti‐HEV may not persist overtime naturally. However, repeat exposure to the virus related to the high prevalence of HEV infection may result in a sustainable specific IgG response.